Integração dos requisitos temporais de um Kernel de tempo-real e de sua comunicação em redes - Rossler, Daniel Augusto (Universidade Federal de São Carlos, 2004)
The study performed on this paper is intended to extend the message exchange between process of a real time kernel, that nowadays is executed between processes on the same station, in order to cover also distinguish stations. In order to allow location transparency to the processes, a name server is used to manage the system processes. And to optimize the server access, the cache and pre-fetching techniques are utilized. Also, during the arrival of a new message to a system node, the Priority Ceiling Protocol will be used to define the priority of the process that will receive the message. As result of this work, it was developed a Real Time Operating System with all the features described above. The name of this Operating System is Sao Carlos.
Keywords: Sistemas operacionais distribuidos (computadores); Tempo real; Rede de computadores; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO